2008
DOI: 10.1039/b804959a
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of lead load and its effect on neonatal behavioral neurological assessment scores in Guiyu, an electronic waste recycling town in China

Abstract: Guiyu is the major electronic waste (e-waste) recycling town in China. The primary purpose of this study was to measure the lead levels in neonates and examine the correlation between lead levels and neurobehavioral development. One hundred full-term neonates from Guiyu and fifty-two neonates from neighboring towns (control group) in the late summer of 2006 were selected for study. The lead levels in the umbilical cord blood (CBPb) and lead levels in meconium (MPb) of neonates were determined with atomic absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(36 citation statements)
references
References 19 publications
(18 reference statements)
1
34
0
Order By: Relevance
“…1,[24][25][26][27] The following findings in this study show that socioeconomic status is also closely associated with prematurity as Barratt scores were lower in the premature groups.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…1,[24][25][26][27] The following findings in this study show that socioeconomic status is also closely associated with prematurity as Barratt scores were lower in the premature groups.…”
Section: Discussionmentioning
confidence: 69%
“…10,[15][16][17] It is noteworthy that lead levels in meconium that were detected by Li et al in Guiyu, an electronic waste recycling town in China, were remarkably lower than in our study and previous reports. 10,27 There have been few studies investigating toxic metal and trace element levels in meconium. In these studies, there were differences in measurement methods, such as using various units for metals and different atomic absorption spectrophotometers (except flame).…”
Section: Discussionmentioning
confidence: 99%
“…Similar toxicology studies at Guiyu e-waste processing sites include Li et al (2007) who find total airborne intake of polychlorinated dibenzo-p-dioxins and dibenzofurans 'far exceed the WHO 1998 tolerable daily intake limit' (Li et al 2007, 5641). Li et al (2008), also studying Guiyu, find a significant correlation between pregnant women's occupation in e-waste recycling and subsequent neonatal lead toxicity with negative effects on neurological development. More recently, Xing et al (2009) have shown that the e-waste processing activities in Guiyu are contributing to the bioaccumulation of high levels of PCBs, including in human breast milk, through inhalation of fumes and through consumption of fish from local water sources.…”
Section: E-waste Researchmentioning
confidence: 99%
“…From this perspective, ewaste is a question of flows of hazardous waste from rich countries being dumped in "pollution havens" (e.g., Neumayer 2001;Clapp 2002) that unfairly burden people and places with toxic effects. A second strand of literature approaches e-waste from the perspective of environmental toxicology and occupational health (e.g., Herat 2008;Li et al 2008Li et al , 2011Nnorom and Osibanjo 2009;Xing et al 2009;Muenhor et al 2010;Tue et al 2010;Wu et al 2010;Chen et al 2011;Fu et al 2011;Wang et al 2011;Lopez et al forthcoming). Here the focus is on the toxicological implications for people and places engaged in particular modes of e-waste processing that put them at high risk of exposure to hazardous matter.…”
Section: Introductionmentioning
confidence: 99%